Pengaruh Pelayanan Prima dan Harga Terhadap Kepuasan Pelanggan Dalam Membentuk Loyalitas Pelanggan Pada UD. Probo Sakti Kota Probolinggo - Mawaddah, Mega Suci; Ngatimun, Ngatimun; Rahajeng, Yekti (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2024)
The purpose of this research is to determine the effect of excellent service and price on customer satisfaction in forming customer loyalty at UD. Probo Sakti, Probolinggo City. This study had 71 respondents as samples. The sampling technique used in this research is a non-probability sampling technique using a purposive sampling technique. Testing was carried out using the SmartPLS 3.2.9 application, which consists of two evaluation models, namely measurement model evaluation (outer model) and structural model evaluation (Inner Model).The research results show that: 1) Excellent service has no effect and is not significant on UD. Probo Sakti customer satisfaction; 2) Price has a positive and significant effect on UD. Probo Sakti customer satisfaction; 3) Customer satisfaction has a positive and significant effect on UD Probo Sakti customer loyalty; 4) Excellent service has a positive effect on UD. Probo Sakti customer loyalty; 5) Price has a positive and significant effect on UD Probo Sakti customer loyalty; 6) Excellent service has no and no significant effect on customer loyalty through UD Probo Sakti customer satisfaction; 7) Price has a positive and significant effect on customer loyalty through UD Probo Sakti customer satisfaction.